Ternary nanoparticles composed of cationic solid lipid nanoparticles, protamine, and DNA for gene delivery - He SN (Dove Medical Press, 2013)
Sai-Nan He,1 Yun-Long Li,1,2 Jing-Jing Yan,2 Wei Zhang,2 Yong-Zhong Du,2 He-Yong Yu,1 Fu-Qiang Hu,2 Hong Yuan21Women’s Hospital, 2College of Pharmaceutical Sciences, School of Medicine, Zhejiang University, Hangzhou, People’s Republic of ChinaBackground: The objective of this research was to design an effective gene delivery system composed of cationic solid lipid nanoparticles (SLNs), protamine, and Deoxyribonucleic acid DNA.Methods: Cationic SLNs were prepared using an aqueous solvent diffusion method with octadecylamine as the cationic lipid material. First, protamine was combined with DNA to form binary protamine/DNA nanoparticles, and the ternary nanoparticle gene delivery system was then obtained by combining binary protamine/DNA nanoparticles with cationic SLNs. The size, zeta potential, and ability of the binary and ternary nanoparticles to compact and protect DNA were characterized. The effect of octadecylamine content in SLNs and the SLNS/DNA ratios on transfection efficiency, cellular uptake and cytotoxicity of the ternary nanoparticles were also assessed using HEK293 cells.Results: When the weight ratio of protamine to DNA reached 1.5:1, the plasmid DNA could be effectively compacted and protected. The average hydrodynamic diameter of the ternary nanoparticles when combined with protamine increased from 188.50 ± 0.26 nm to 259.33 ± 3.44 nm, and the zeta potential increased from 25.50 ± 3.30 mV to 33.40 ± 2.80 mV when the weight ratio of SLNs to DNA increased from 16/3 to 80/3. The ternary nanoparticles showed high gene transfection efficiency compared with LipofectamineTM 2000/DNA nanoparticles. Several factors that might affect gene transfection efficiency, such as content and composition of SLNs, post-transfection time, and serum were examined. The ternary nanoparticles composed of SLNs with 15 wt% octadecylamine (50/3 weight ratio of SLNs to DNA) showed the best transfection efficiency (26.13% ± 5.22%) in the presence of serum. It was also found that cellular uptake of the ternary nanoparticles was better than that of the SLN/DNA and binary protamine/DNA nanoparticle systems, and DNA could be transported to the nucleus.Conclusion: SLNs enhanced entry of binary protamine/DNA nanoparticles into the cell, and protamine protected DNA from enzyme degradation and transported DNA into the nucleus. Compared with Lipofectamine 2000/DNA nanoparticles, these cationic ternary nanoparticles showed relatively durable and stable gene transfection in the presence of serum.Keywords: solid lipid nanoparticles, protamine, plasmid DNA, gene transfection, ternary nanoparticles